PENDAMPINGAN PENGEMBANGAN USAHA MUSTAHIQ BINAAN LAZISMU GRESIK - Aufa, Muhammad; Ismanto, Hadi (Jurnal Pengabdian Masyarakat dan Lingkungan, 2022)
Lazismu PDM Gresik has implemented a community empowerment program by providing capital for mustahik. The purpose of this activity is to change the status of mustahik to become independent business actors. As part of Muhammadiyah's business charity, this empowerment activity is not only related to economic problems, but also as part of da'wah to strengthen monotheism of business actors. The target group for this service consists of business actors who have received capital from Lazismu PDM Gresik funds. The priority problem that is still being faced is business management and the presentation of its financial statements. The implementation of PKM activities will be carried out by transferring knowledge and technology (IPTEK) by conducting coaching activities such as counseling. After the counseling, assistance will be provided by the Student Team to oversee the preparation of financial reports. The results of this community service are: Knowledge and understanding in business development (innovation), and understanding business financial records through the android application, as well as improving infrastructure in developing a business.